2013
DOI: 10.1186/1742-9994-10-67
|View full text |Cite
|
Sign up to set email alerts
|

Tadpole transport logistics in a Neotropical poison frog: indications for strategic planning and adaptive plasticity in anuran parental care

Abstract: IntroductionIndividuals should aim to adjust their parental behaviours in order to maximize the success of their offspring but minimize associated costs. Plasticity in parental care is well documented from various bird, mammal and fish species, whereas amphibians were traditionally assumed as being highly instinct-bound. Therefore, little is known about ‘higher’ cognitive abilities of amphibians, such as strategic planning and behavioural flexibility. Dendrobatid frogs have evolved a remarkable diversity of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
120
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 61 publications
1
120
0
Order By: Relevance
“…In A. femoralis the likelihood for males to encounter foreign clutches inside their own, established territory can be considered rather low as territories are vigorously defended physically against male intruders41. This notion is further supported by a previous study which reported only four (3%) out of 119 tadpole transporting males carrying unrelated tadpoles (in three cases the tadpoles of neighbouring individuals) on their back45. By following the simple decision rule ‘transport all clutches inside and eat all clutches outside my territory’, male A. femoralis reduce both the risk of accidentally rejecting own offspring at the time a territory has been established as well as the risk of misdirected care at locations where the likelihood of paternity is low.…”
Section: Discussionmentioning
confidence: 86%
“…In A. femoralis the likelihood for males to encounter foreign clutches inside their own, established territory can be considered rather low as territories are vigorously defended physically against male intruders41. This notion is further supported by a previous study which reported only four (3%) out of 119 tadpole transporting males carrying unrelated tadpoles (in three cases the tadpoles of neighbouring individuals) on their back45. By following the simple decision rule ‘transport all clutches inside and eat all clutches outside my territory’, male A. femoralis reduce both the risk of accidentally rejecting own offspring at the time a territory has been established as well as the risk of misdirected care at locations where the likelihood of paternity is low.…”
Section: Discussionmentioning
confidence: 86%
“…These characteristics are shared with many other Allobates species with exotrophic tadpoles including A. femoralis, the best-studied congeneric species regarding parental care (e.g., Ringler et al 2013Ringler et al , 2015. Male A. subfolionidificans visited egg clutches regularly, probably to hydrate them, and took concomitant care of more than one clutch.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in species such as Allobates masniger (Morales 2002) and Allobates nidicola (Caldwell and Lima 2003) eggs hatch into endotrophic tadpoles that complete development in a terrestrial nest. Reproductive modes found in Allobates comprise many behavioral particularities that include 1) the use of a large repertory of visual, acoustic and tactile signals during long interactions for courtship and mating such as in A. caeruleodactylus (Lima et al 2002) and A. femoralis (Boulenger 1884) (Montanarin et al 2011), 2) the use of different oviposition sites such as foam nests constructed by leptodactylids in A. sumtuosus Morales 2002 (Kok and Ernst 2007), fallen leaves on the forest floor by A. marchesianus (Melin 1941) (Lima and Keller 2003) and bromeliads by A. bromelicola (Test 1956), as well as 3) intersexual flexibility in parental care as observed in Allobates femoralis (e.g., Ringler et al 2013Ringler et al , 2015. Many aspects of these behaviors are completely unknown for most species of dendrobatoid (Dendrobatidae + Aromobatidae) frogs, especially due to the high rate of species descriptions within the genus.…”
Section: Introductionmentioning
confidence: 99%
“…In other taxa with larval transport, larval survivorship is high and parents sometimes carry entire clutches and distribute their offspring in different pools when available, but also travel long distances if suitable sites are rare (Ringler, Pasukonis, Hödl, & Ringler, 2013). Thus, we cannot explain the low number of tadpoles per deposition in L. palavanensis without further studies in offspring survival and larval transport logistics.…”
Section: Discussionmentioning
confidence: 87%